Global Trends in Childhood Immunization Research: A Bibliometric Analysis of Publications from 1974 to 2025 - Noya, Josephus; Kusumawati, Ira; Lameky, Vernando Yanry; Batlajery, Belfrit Victor; Syaripudin, Ahmad; Sillehu, Sahrir (Trends in Immunotherapy, 2025)
Childhood immunization is a crucial public health intervention for preventing infectious diseases and reducing mortality. However, global immunization coverage faces challenges such as inequality in vaccine access, the rise of anti-vaccination movements, and the impact of the COVID-19 pandemic. This study aims to analyze global research trends in childhood immunization using a bibliometric approach. Data were collected from the Scopus database, and 629 research articles published between 1974 and 2025 were included in the analysis. The results showed a significant increase in publications over the decades, peaking in 2022. The United States, India, and China were the top contributors, while collaboration patterns revealed the United States and the United Kingdom as the main hubs of the global research network. The research focused on public health, vaccines, child health, and infectious diseases. The study also identified research gaps, including the need for more contextualized studies in developing countries and the integration of technological innovations. Future research should focus on interventions to reduce immunization pain, improve health systems, and address sociocultural barriers to immunization coverage. These findings provide valuable insights for policymakers, health practitioners, and researchers to strengthen childhood immunization programs and promote global child health.